Correction : Molecular diagnosis of Chagas disease in Colombia : Parasitic loads and discrete typing units in patients from acute and chronic phases (2016)
Fe de erratas. The fifth author's name is spelled incorrectly. The correct name is: Carlos A. Valencia-Hernandez. The correct citation is: Hernández C, Cucunubá Z, Flórez C, Olivera M, Valencia-Hernandez C.A., Zambrano P, et al. (2016) Molecular Diagnosis of Chagas Disease in Colombia: Parasitic Loads and Discrete Typing Units in Patients from Acute and Chronic Phases. PLoS Negl Trop Dis 10(9): e0004997. doi: 10.1371/journal.pntd.0004997